Penyuluhan Bagi Warga dan Tokoh Masyarakat Tentang Pertumbuhan dan Perkembangan untuk Meningkatkan Karakter Anak - Ayi Najmul Hidayat; Kingking Muttaqien (LPPM UNINUS, 2017)
The succes of character education can be influenced by the understanding of citizens and public figure on the development and growth of children. Every children has different abilities in carrying out developmental tasks , developing aspects and characteristic of development . Based on the results of preliminary research shows that the citizens and public figure in the village Ciomas district panjalu, ciamis district still lack understanding of development and growth of children. One way to improve the understanding of citizens and public figure through counseling with the aim of improving the character of children based on the growth and development of children . The methods in counseling are discourse and discussion. The results of this counseling can be increase the motivation of citizens and public figure to understand the importance of growth and development of children and expect re-counseling. Citizens and public figure motivation is an indicator of successful implementation of counseling.